Maize-bean intercropping mediates reduction in arthropod intraguild predation better than low-intensity farming—Stable isotope evidence - Nickson Erick Otieno; James Stephen Pryke; Jonathan Mukasi (PLoS ONE, 2025)
Crop-field structural management for boosting arthropod pest bio-control is increasingly recognized as an environmentally sustainable alternative to chemical pesticides. However, how natural pest regulation outcomes may be undermined by intraguild predation among pest natural enemies is seldom investigated in cereal crops-fields. Here we use δ13C and δ15N stable isotope analyses to assess intraguild predation amongst five arthropod taxa, comparing this to their consumption of three pest taxa, and test how such patterns relate to farming system (low-intensity/conventional) or cropping method (monoculture/intercropping) across 15 small non-transgenic maize fields. Overall, consumption of pests exceeded intraguild predation, especially Lepidoptera contribution to wasp, predatory beetle and predatory bug diets. However, every predatory taxon integrated diet carbon from all the others, particularly from predatory bugs. Predatory beetles showed the strongest connection to pest consumption while predatory bugs had the strongest connection to intraguild diet carbon. In general, wasps, predatory beetles and spiders exhibited more significant orientation towards pest consumption while predatory bugs were more of intraguild predators, but ants incorporated both food-sources nearly proportionately. Regarding influence of cropping options, pest consumption exceeded intraguild predation in intercropped compared to monoculture farms while for farming system, low-intensity rather than conventional systems promoted higher consumption of Lepidoptera pests. Low-intensity farming also enhanced intraguild consumption of predatory bugs. By contrast, while conventional farming boosted beetle and bug pest consumption, it was also associated with enhanced intraguild predation overall. Generally, therefore, field-level maize-field structural complexity through intercropping may be more impactful than chemical-free farming for mediating intraguild predation and hence boosting natural pest suppression. These findings, the first to quantitatively compare multiple-taxa pest consumption to intraguild predation in maize-fields, are important in informing appropriate agronomic management interventions within cereal-crop farming landscapes to maximize top-down pest biocontrol.